An Appraisal of the Attitudes and Achievement Motivation of Arab Postgraduate Students Towards the Learning of the English Language in Selected Malaysian Public Universities - Idris, Mariam Oluwatoyin; Yusuf, Muhammed; Mohd Hanif, Mohd Hafis; Adekunle, Salisu Monsuru; Kayode, Bakare Kazeem (Asian Journal of Assessment in Teaching and Learning, 2021)
Motivation and Attitude, being linked frequently to actual classroom studying situations, are very significant and crucial contributing elements within the second language learning process. The role of attitude and motivation in the acquisition of foreign languages has been a major concern to foreign language researchers. Attitude and motivation are known as essential and distinctive thoughts in social sciences. They have as well maintained their position as a central concept on the field. Attitude is an essential part of understanding human behaviour and it is considered as a mental state that includes feelings and beliefs. In this systematic review, the researchers explain the concept of attitude and its models, attitudes and language acquisition, and achievement motivation and its theories. The review of related literature shows that Arab postgraduate students have some positive attitudes towards the learning of the English Language and are also motivated towards the learning of the English Language.